Ripening evolution in double pruning management of french grapevines 'merlot' and 'tannat' under subtropical conditions in Brazil. - MANIERO, C. R. (2024)
Brazil boasts continental dimensions and a vast diversity of viticulturewithinitsterritory,withaplantedareaexceeding75million ha.Wineproduction surgedby 60%in2020, accompaniedby a 1.2%expansion invineyardacreage,markinga recordsince the 2000s.Withthepursuitofnewviticultural frontiersandtheincreased productionofwines,particularlyfromFrenchgrapevarietiessuchas 'Merlot' and 'Tannat', new cultivation techniques have been developed to enhance grape ripening and consequently the productionofqualitywines,especially inregionswithnotraditionin viticulture.Thedualpruningtechnique,still relativelynovel inBrazil, originatedintheBrazilianSoutheastandisemployedforproducing winesofsuperiorqualityinsubtropicalhigh-altitudeconditions